Estimating the impact of metabolic syndrome on low back pain and the joint effects of metabolic syndrome and depressive symptoms on low back pain: insights from the China Health and Retirement Longitudinal Study - Jinghong Huang; Dongrui Peng; Xiaohui Wang (BMC, 2024)
Abstract Background Although metabolic syndrome (MetS) and depressive symptoms (DS) are predictors of low back pain (LBP), their combined effects and relative contributions to LBP have not been well studied. Using the nationally representative data from the China Health and Retirement Longitudinal Study (CHARLS), this study conducted cross-sectional and longitudinal analyses to investigate the impact of MetS on LBP, and the joint effects of MetS and DS on LBP. Methods This study included a cross-sectional analysis of 8957 participants aged at least 45 years from the CHARLS 2011 dataset and a longitudinal follow-up of 3468 participants without LBP from the CHARLS 2011, tracked over 9.25 years (from June 2011 to September 2020) with 4 times LBP assessment in CHARLS 2013, 2015, 2018, and 2020. To explore the association between MetS on LBP and the joint effects of MetS and DS on LBP, multivariable-adjusted multinomial logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Multivariable-adjusted COX proportional hazards regression models were applied to estimate hazard ratios (HRs) and 95% CIs. All statistical analyses were conducted using STATA (version SE16). Results In the cross-sectional analysis, MetS was associated with a lower risk of LBP (adjusted OR = 0.85, 95% CI = 0.74-0.97), while there was no significance for this association in the longitudinal analysis. In the joint association of MetS and DS with LBP, participants with NoMetS + DS (adjusted OR = 2.31, 95% CI = 1.94-2.75), and MetS + DS (adjusted OR = 2.16, 95% CI = 1.81-2.59) were risk factors for LBP events, while those with MetS + NoDS (adjusted OR = 0.75, 95% CI = 0.62-0.90) was a protective factor for LBP events than those with NoMetS + NoDS. During the 9.25 years of follow-up, 1708 cases (49.25%) experienced incident LBP events. In the longitudinal analysis, a significantly negative association was not found in MetS + NoDS for LBP events. Three sensitivity analyses identified the robustness of the associations. Moreover, the nature of cross-sectional associations differed by age (45-64 and 65 + years). Conclusions Our study found that MetS was linked to a lower incidence of LBP, but this effect does not persist over time. Importantly, the combination of MetS and DS significantly increased LBP risk, a joint effect not extensively studied before. These findings underscore the novel contribution of our research, advocating for the joint assessment of MetS and DS to enhance LBP risk stratification and inform prevention strategies.